The European bison (Bison bonasus l.) population status in theWestern region of Ukraine (European Bison Conservation Newsletter, 2009)
Restitution of the European bison in the Western region of Ukraine began in the second half of the 20th century. For the period from 1965 to 1982 the European bison were brought to 5 regions. To the Volyn region, 15 individuals were brought from the Byelovezskaja Pushcha (Byelorussia) in 1965. The highest population number (approximately 200 individuals) the herd reached at the beginning of the 1990s. Since 1992 population is on decrease. During the period between 1992 and 2003, 28 individuals died from various reasons. There have been registered bison migrations outside their home ranges on a distance of 40 – 45 km, and the poaching. Trophy hunting was organised for foreign hunters. During 1991–1999 foreigners bagged there in total 29 European bison. As of 2009 the population is estimated on 15–20 individuals. There are two populations of the European bison in the Lwow region: one in the mountain part, other – in the lowlands. Ten wisents captured from Byelovezskaja Pushcha were brought to the mountain part in 1965. The mountain population in mid of the 1990s counted over 30 individuals. Existence of this group is threatened because of considerable decrease of the number. To improve the situation, this herd will be supplemented with genetically selected animals, imported from abroad this June, which after the acclimatisation period will be released to the wild. To the lowland part of the oblast the European bison 6 individuals were brought from Lithuania in 1980. Unfortunately, those animals reproduced badly, there some single individuals migrated to the territory of the nearby Rivne and Ternopil regions. At the beginning of 21st century remained there only 6–8 individuals. With the purpose of population renewal during 2008–2009 new animals were brought from the Vinnytsia region. As of June 2009 this population counts approximately 25 individuals. To the Rivne region, 8 individuals were brought from Belavezskaya Pushcha in 1967. This population ceased to exist in 1978. In 1970 to the hunting grounds of the Tchernivtsi oblast 19 European bison were brought from Berezinskoy (Byelorussia), Okskoy and Prioksko-Terrasny (Russia) preserves. In 1994–1995 this population reached its highest numbers – near 225 individuals. However, since 1996 it decreased to about 70 individuals in 2009.
Keywords: Ukraine; Bison bonasus; restitution; population numbers